2020
DOI: 10.35760/jpp.2020.v4i1.2655
|View full text |Cite
|
Sign up to set email alerts
|

FITOTOKSISITAS KINERJA HERBISIDA OKSIFLOURFEN DAN GLIFOSAT PADA KACANG FABA (Vicia faba L.)

Abstract: Penelitian ini dilakukan di Laboratorium Farmakologi Fakultas Pertanian Universitas Thessaly dengan membahas efek herbisida oksifluorfen, glifosat terhadap tanaman kacang faba. Herbisida oksifluorfen mengandung bahan aktif oksifluorfen yang termasuk dalam kelompok kimia eter difenil. Mekanisme kerja herbisida ini adalah menargetkan enzim protoporphyrogen oksidase (Protox) dan protoporphyrin IX (Protogen IX). Pengamatan dilakukan dengan tujuan mengetahui dan mengevaluasi fitotoksisitas aplikasi herbisida terhad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…In this case, social media talks a lot about the product, and social users talk a lot about the positive value of the product, besides that many consumers recommend using the product, some of which make e-WOM influence purchasing decisions. This is in line with previous research conducted by (Perkasa et al, 2020), which stated that comments and reviews are an essential factor that helps Saudi consumers make purchasing decisions. More than 80% of study participants indicated that they read online reviews before making an online purchase.…”
Section: The Influence Of E-wom On Purchasing Decisionssupporting
confidence: 92%
“…In this case, social media talks a lot about the product, and social users talk a lot about the positive value of the product, besides that many consumers recommend using the product, some of which make e-WOM influence purchasing decisions. This is in line with previous research conducted by (Perkasa et al, 2020), which stated that comments and reviews are an essential factor that helps Saudi consumers make purchasing decisions. More than 80% of study participants indicated that they read online reviews before making an online purchase.…”
Section: The Influence Of E-wom On Purchasing Decisionssupporting
confidence: 92%
“…Padi merupakan tanaman yang termasuk ke dalam kelompok tanaman C3. Tanaman C3 merupakan tanaman yang lebih adaptif dengan kondisi yang memiliki kandungan CO2 tinggi pada atmosfer (Perkasa et al 2017). Secara umum, padi membutuhkan waktu sekitar 120 hari hingga panen.…”
Section: Karakteristik Spektral Padiunclassified
“…Increasing the number of stomata is related directly proportional to the CO2 that can be fixed. Based on differences in carbon dioxide fixation, B rapa chinensis L plants included in C3 plants (Perkasa et al, 2017).…”
Section: Figure 7 Average Total Stomatamentioning
confidence: 99%